Daya Hidup Spermatozoa Epididimis Kambing Peranakan Ettawa yang Dipreservasi dengan Pengencer Tris dan Bberbagai Konsentrasi Maltosa - Muhammad Rizal; Dwi Sulistiowati; Abrani Sulaiman; Herdis Herdis; Insun Sangadji (Jurnal Sain Veteriner, 2016)
Cauda epididymal spermatozoa could be used as an alternative source of gamete in the application of various reproductive technologies, since the spermatozoa is motile and has ability for fertilizing the oocyte. Theobjective of this research was to examine the effectivity of maltose in maintaining viability of ettawa crossbreed goat epididymal spermatozoa preserved at 3–5oC. Five testis with epididymides of ettawa crossbreed goat were obtained from slaughterhouse. Epididymal spermatozoa was collected by the combination of slicing, flushing and tissues pressure of cauda epididymides with physiological saline (0.9% NaCl). Collected-spermatozoa wasdivided in equal volume into three tubes and diluted with Tris extender containing 20% egg yolk (control), Tris extender + 0.3 g maltose/100 ml (M0.3), and Tris extender + 0.6 g maltose/100 ml (M0.6), respectively. Dilutedspermatozoa was stored in refrigerator at 3–5oC. Quality of diluted-spermatozoa including percentages of motile spermatozoa (MS) and live spermatozoa (LS) were evaluated every day during storage at 3–5oC for four days. Data were analyzed using completely randomized design with three treatments and five replicates. Means were compared significant difference test at 0.05 significant level. Results of this study showed that mean spermatozoaconcentration, percentage of MS, percentage of LS, and percentage of abnormal spermatozoa of ettawa crossbreed goat fresh epididymal spermatozoa were 3,220 million cell/ml, 70%, 81%, and 4.3%, respectively. At day-5 of storage, percentages of MS and LS for M0.3 (38 and 60.4%) and M0.6 (38 and 57.2%) were significantly (P<0.05) higher than control (32 and 55.4%). In conclusion, addition of 0.3 and 0.6% maltose in Tris extender could be maintained viability of ettawa crossbreed goat epididymal spermatozoa preserved at 3–5oC forthree days.